Beyond Magna Carta : - Blick, Andrew (Hart Publishing, 2015)
This book, published at the time of the 800th anniversary of Magna Carta, considers a series of historical documents from Anglo-Saxon times onwards which sought to set out arrangements for the governance of England and later the UK as a whole